An enabling mechanism for the creation, adjustment, and dissolution of states and governmental units - Kjell Hausken; John F. Knutsen (Kiel Institute for the World Economy (IfW), 2010)
The article proposes an enabling mechanism for the creation, adjustment and dissolution of governmental units, giving autonomy to each individual as in a direct democracy. The mechanism is designed such that Pareto optimality is possible, in contrast to earlier models which make various assumptions such as majority voting. Individuals are taken seriously acknowledging that they are best equipped to find their own solutions. The emphasis is on the practical approach of how individuals discover and implement their subjective preferences and how this discovery and implementation process can be facilitated and corresponding costs lowered. Governmental units are subjected to some of the same market forces as business firms. This brings the interaction between governmental units closer to a market structure, and serves to eliminate or reduce many of the coercive elements of government.
Keywords: H4; H5; H11; 330; Territorial units; individual liberty; individual decision making; individual welfare; competitive markets; public choice; governmental units; endogenous determination of borders; constitutional economics; political economy